Politik Hukum Digital Banking di Indonesia - Muhammad Wildan Ichsandi; Gunardi Lie (CV Rewang Rencang, 2024)
This research aims to analyze the legal politics of digital banking in Indonesia in the context of protecting the personal data of digital banking customers. The method employed in this study is normative juridical, using statutory and conceptual approaches. The legal politics of digital banking in Indonesia are directed towards providing legal protection for customer data amidst the rapid development of financial technology. The government has formulated various regulations, such as the ITE Law and regulations issued by the Financial Services Authority, to safeguard the digital banking system from cybercrime. Nevertheless, challenges remain in implementing these regulations due to infrastructural disparities and low levels of digital literacy among the public. In addition, coordination between law enforcement agencies and financial authorities needs to be strengthened to ensure effective customer protection. Therefore, digital banking legal policies must be responsive to technological advancements and capable of upholding consumer rights. In conclusion, regulatory harmonization and institutional capacity-building are essential to achieving optimal legal protection in the digital banking sector.